Rational design synthesis and optimization of manganese-based cathode materials for lithium-ion batteries - Haruna, Aderemi Bashiru (My University, 2020)
This Ph.D. thesis strategically investigated some synthetic methods aimed at tuning the physico-chemistry and electrochemical properties of two manganese-based spinel cathode materials (i.e., LiMn2O4 (LMO) and LiMn1.5Ni0.5O4 (LMNO)) for Li-ion batteries. For the LMO, pristine commercial LMO material (LMO-p) was subjected to microwave irradiation process to obtain a modified LMO material (LMO-m). The effects of microwave irradiation on these two materials were thoroughly studied using different advanced techniques, including synchrotron powder x-ray diffraction (SPXRD), x-ray photoelectron spectroscopy (SXPS), powder neutron diffraction (PND), Solid-State Magic-Angle-Spinning Lithium Nuclear Magnetic Resonance (MAS 7Li NMR), Raman spectroscopy, thermogravimetric analysis(TGA) and Nitrogen Gas Adsorption analysis. TGA results reveal that the LMO-m sample is more thermally stable than the LMO-p sample. The Nitrogen Gas Adsorption analysis results show that the LMO-m has a larger surface-area, pore-volume and pore-size than LMO-p. Nitrogen Gas Adsorption analysis, SXRD, SXPS, 7Li MAS NMR and PND consistently prove that microwave irradiation has increased the Mn4+content in LMO-m more than in the LMO-p. Electrochemistry techniques (i.e., cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS)and galvanostatic charge-discharge (GC-D)) show that LMO-m possesses faster electron transfer kinetics, mass transport, better reversibility (Coulombic efficiency), higher specific capacity, and higher conductivity than the LMO-p. For the first time, this study has shown that microwave irradiation can suppress Jahn-Teller distortion and improve the physical and electrochemical properties of LMO without the conventional doping or surface-coating. For the LMNO, for the first time, two simple strategic alternative synthetic routes were used to synthesize LMNO cathode materials from -MnO2-δwith different contents of oxygen vacancy. One was obtained in argon atmosphere (LMNO-Ar) and the other in high reducing hydrogen atmosphere (LMNO-H2). The TGA, SPXRD, Raman spectroscopy and GC-D reveal that LMNO-Ar has better structural stability than LMNO-H2, while SPXRD, FTIR, Raman, XANES, CV and GC-D show that the two samples have both disorder and order phases. The SPRXD, PND, SXPS, CV and GC-D revealed that LMNO-H2has greater Mn3+content than the LMNO-Ar and thus directly reflects oxygen vacancy contents in the two cathode materials. The CV, GC-D and EIS show that the LMNO-H2is more conductive than LMNO-Ar. The GC-D reveals that LMNO-H2has a better specific capacity (113.6 mAhg-1) than that of LMNO-Ar (90.1 mAhg-1) but has worse capacity retention of (48.3%) than that LMNO-Ar (77.6%). The TEM images show that the two samples are nanorods. The results reveal that the oxygen vacancies change concurrently with the degree of disorder and amount of Mn3+.The discharge capacity increases with oxygen vacancies, degree of disorder and amount of Mn3+, while the retention capacity decreases with increasing with oxygen vacancies, disorder and amount of Mn3+. These studies reveal strategic processes that can be adapted in the design, synthesis and optimization of the spinel Mn-based cathode materials for Li-ion batteries
A thesis submitted in fulfilment of the requirements of the degree of Doctor of Philosophy (PhD), in the Faculty of Science, University of the Witwatersrand, 2020